Key Elements of Innovative Administration to Build Smart Cities (Acta Universitatis Danubius. Œconomica, 2024)
Innovation in public administration as a „mode” of functioning may greatly contribute to creating new avenues of development for entire local communities that can be transformed into more inclusive, better equipped to respond to citizens’ needs and resilient communities.The article also pursues the objective of emphasizing the links (and the complexities of these links) between local government or local public administration, innovation and the specific elements or aspects that are fundamental in creating or transforming cities into smart ones. As already established by the scientific literature of the last decade, innovation does take place in the public sector and embraces several specific forms or categories which can become instruments of great improvement of the quality of government, at both national and local level.